Public-private partnership - socio-economic and innovative development of university clinics - V. D. Chopchik (Kazimierz Wielki University, 2019)
Objective: To substantiate the development of university clinics (UC) through innovative entrepreneurship based on the mechanism of public-private partnership (PPP). Materials and methods. The general scientific methods of analysis, synthesis, integration, interpretation of scientific data, as well as systemic and structural-functional approaches. The information base of the study was the scientific works of domestic and foreign experts in innovation and PPP. Introduction. The unsatisfactory financing system for university clinics determines the existence the outdated material and technical base, lack of modern medical technologies, low level of staff remuneration, and lack of economic motivation to work in the staff. All this requires improving UC's management. International experience accumulated over the past 25-30 years suggests that one of the main mechanisms for improving public health management is innovative entrepreneurship. The organization of PPPs as the main direction of development of medical faculties, ensuring the interaction of education, science and innovation, as a key element of state policy to stimulate the health sector, cooperation in the framework of the "knowledge triangle" can be traced to Norway example. Currently, one of the priority areas for the development of PPP mechanisms is the implementation of an economic policy for the accelerated development of innovative entrepreneurship. This is due both to the very nature of global competition, based on the advanced use of advanced innovations, and to the competition intensification between economic systems for development resources. Innovation is a driver of economic growth and a significant competitive advantage. Results. In the article presented the development of UCs focused on their innovative functioning as a high-tech medical sector and is consistent with their targeted program planning based on the complex relationship of three systems: the State, the UC and the scientific cooperation system (university). The economic component makes it necessary to introduce a new form of organizing the activities of the UC on the principles of PPP. Conclusions. In the article presented  the process of UC development based on the principles of PPP is scrutinazed.